Sedative Choice: The Chilling Confounder to Targeted Temperature Management - W. Anthony Hawkins; Aliya Abdulla; Xiaodong Hua; Andrea Sikora (University of Minnesota Libraries Publishing, 2022)
Targeted temperature management (TTM) is a technique used in adults who lack a meaningful response after the return of spontaneous circulation following cardiac arrest (CA). The implementation of TTM is believed to improve neurological outcomes by decreasing cerebral metabolism, reducing apoptosis, and lowering oxygen demand. While this technique is recommended as a part of advanced cardiovascular life support (ACLS), there is a lack of consistency regarding drug choice and depth of sedation in TTM. In this report, the authors provide a review of the myriad of regimens outlined in research protocols and current guidelines to stimulate discussion and promote further studies pertaining to sedation strategies in TTM. Through this call to action, the ultimate goal is to develop a uniform approach to bedside practice.